Teachers’ and Parents’ Perceptions on Eating Behaviour of Primary School Students: A Qualitative Study - Acharya, Milan; Acharya, Kamal Prasad (Journal of Health Promotion, 2020)
This study explores the perceptions involved in the healthy eating behaviour of 1st, 2nd, and 3rd-grade students in a primary level community school in Nepal. A total, ten observations during mid-day meal and three focus group discussions were conducted among teachers and parents. Sixty students from grade one to three, five teachers and sixteen parents took part in the study. All the participating teachers and parents were engaged in dialogue conferences during focus groups and students’ eating behaviours were observed by the teachers and parents during tiffin time throughout the study. Thematic-content analysis based on the qualitative approach was used on the collected data from the field notes during a series of participant observations and focus group discussions. It is found that the family norms and feeding culture around a child’s domestic life have an active role in establishing and promoting healthy habits that persists throughout. It is also noted that parental food habits and feeding strategies are the most dominant determinants of children eating behaviour and food choices of mid-day meal during tiffin time at the school. It is recommended that parents and teachers should expose their children and students to a range of good food choices and acting as positive role models.